KAJIAN FAKTOR GEOGRAFI UNTUK INDEKS KESESUAIAN TAMBAK GARAM DI DESA LETE KONDA KECAMATAN LOURA KABUPATEN SUMBA BARAT DAYA - Ngongo, Yohanes Ledi; Sunimbar, Sunimbar; Hasan, Muhammad Husain (Jurnal Geografi, 2022)
This study aims to determine the geographical factors for the salt suitability index ini Lete Konda village, to the determine the geographical factors for the salt saitability index in lete konda village, loura district, southwest sumba district. The method used in this study is the matching method with observation data. This research was conduted in the village of lete konda. The type of research used in this study is a quantitative descriptive research using the IKG salt suitability index analisys method. The data documentation. Geographic factor analisys is measured using the IKG salt suitability inndex, to be able to determine the suitability of geographical factors at the location salt production. Based on the resuts of the analisys, it is known that the geographical factor for the salt suitability index in lete konda village, loura district,southwest sumba regency for rainfall is not suitable (S2) soil permeability is quite suitable (S1), sun exposure is conditionally appropriate (S2), air humidity is very low. Soutable (S1), wind speed is quite suitable (S2), air temperature is very suitable (S1), evaporatin is quite suitable (S2), water saturation is conditionally appropriareta (S1), soil texture is quite flare (S2), seawater salinity is very suitable (S1). Geographical factors for the salt suitabilty index are very suitable, quit suitable,condisitionally appropriare, and not suitable.